Lateral approach for resection of the C3 corpus: technical case report - (:unkn) unknown (My University, 2003)
OBJECTIVE AND IMPORTANCE: The C3 level is the transition zone between the upper and lower cervical spine. Because of its high position and anatomic relationships to significant structures, exposing C3 is challenging, and the surgical approach is controversial. CLINICAL PRESENTATION: A 16-year-old girl was admitted to our institution with a 3-year history of neck pain and progressive quadriparesis. Neuroradiological examination revealed severe spinal cord compression from kyphosis at the C3 level. TECHNIQUE: We used the lateral approach to resect the C3 corpus and realign the cervical spine. Resecting the transverse processes of C2-C4 and mobilizing the V2 segment of the vertebral artery adequately exposed C3 for resection. Bilateral occipitocervical fusion was performed in a second procedure, and no postoperative complications occurred. The patient's neurological status improved drastically after surgery, and she has had no craniocervical instability during the follow-up period. CONCLUSION: The lateral approach to the C3 corpus offers the greatest degree of cord decompression and easy access to the lesion in a wide and sterile operative field. We describe the surgical technique of this approach as an alternative to the anterior transmucosal or anterolateral retropharyngeal approach.
Keywords: Female; Humans; Postoperative Complications; Adolescent; Cervical Vertebrae; Decompression, Surgical; Neurologic Examination; Spinal Cord Compression; Kyphosis; Spinal Fusion